Role of hypothalamic neuropeptides in feed intake regulation of livestock species (literary review) - Simon, Ádám; Jávor, András; Czeglédi, Levente (Acta Agraria Debreceniensis, 2015)
Energy balance is the net result of the energy intake (nutrition) and expenditure (basic metabolic rate). The purpose of the daily feed intake is to provide energy and nutrients for maintenance, production and fill and maintain energy storages in form of glycogen and fat. Animals can adjust their feed intake to ensure their energy demand. Food intake regulation in animals and human is a very complex process, in which the digestive system, the central nervous system, the joining hormonal and non-hormonal factors, and the integrating hypothalamus take part. This review primarily focuses on the action mechanism of some important appetite regulating neuropeptides, and their impacts on the performance traits of the economically significant animal species.